2005
DOI: 10.1093/rpd/nci111
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of germanium detector calibration using the Monte Carlo method: comparison between point and surface source models

Abstract: Simulation of detector calibration using the Monte Carlo method is very convenient. The computational calibration procedure using the MCNP code was validated by comparing results of the simulation with laboratory measurements. The standard source used for this validation was a disc-shaped filter where fission and activation products were deposited. Some discrepancies between the MCNP results and laboratory measurements were attributed to the point source model adopted. In this paper, the standard source has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Traditionally, the response of a HPGe detector for gamma/X-rays is determined empirically using radioactive sources of known activities. In recent years, there is a growing trend in utilizing Monte-Carlo simulations to study properties related to the detection and quantification of gamma/X-ray by radiation detectors, including detection efficiency, cascade summing effect, evaluation of detector internal dimensions, impact of shielding materials over the MDA, optimization of detector configuration and the full reconstruction of a gamma-ray spectrum [1][2][3][4][5][6][7][8][9]. The main advantages of using numerical calculations are versatility, reduced cost and avoiding the risks associated with handing of radioactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the response of a HPGe detector for gamma/X-rays is determined empirically using radioactive sources of known activities. In recent years, there is a growing trend in utilizing Monte-Carlo simulations to study properties related to the detection and quantification of gamma/X-ray by radiation detectors, including detection efficiency, cascade summing effect, evaluation of detector internal dimensions, impact of shielding materials over the MDA, optimization of detector configuration and the full reconstruction of a gamma-ray spectrum [1][2][3][4][5][6][7][8][9]. The main advantages of using numerical calculations are versatility, reduced cost and avoiding the risks associated with handing of radioactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their studies, they suggested that for good photon detection the ratio of source-detector distance (d) to detector radius (R) should be less than 0.01. It should be noted at this point that from the point of view of radiation protection these criteria cannot be justified in certain circumstances, for instance, when the area to be monitored presents high background radiation level or contaminated by sources of high radiation level [6,7]. Radiation protection regulation requires that exposure of radiation to personnel should be kept as low as reasonably achievable.…”
Section: Introductionmentioning
confidence: 99%
“…(2005). [10] This tally with Gaussian energy broadening code can resembles the output simulation pulse of the detector from photons with energy E through three various factors a, b, and c.[11] Relation between full width at half maximum (FWHM) and these factors are defined as ;[12] therefore, these factors can be achieved measuring FWHM of a detector at least for three different sources.…”
Section: Methodsmentioning
confidence: 99%